A dual-core photovoltaic waterproof cable and a preparation method thereof

CN116631683BActive Publication Date: 2026-10-13SHANGHAI JINYOU JINHONG INTELLIGENT ELECTRIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310818870.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2026-10-13
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

双芯光伏电缆相对于单芯光伏电缆,提高了导电性能和电力传输性能,减少了传输过程中的电力损失,并提高了光伏电缆的抗拉强度,双芯光伏电缆都需户外敷设,环境条件较为恶劣,虽具有较高的抗拉强度,但防水性差,难以满足潮湿盐雾环境的使用需求

Benefits of technology

(1)本申请通过控制双芯光伏电缆的各原料种类和掺量,使双芯光伏防水电缆经耐水试验后的抗张强度、断裂伸长率和体积电阻保留率分别为87%、88%和95%,提高了双芯光伏电缆的防水性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004322793150000061
    Figure BDA0004322793150000061
  • Figure BDA0004322793150000071
    Figure BDA0004322793150000071
  • Figure BDA0004322793150000081
    Figure BDA0004322793150000081
Patent Text Reader

Abstract

The application relates to the technical field of cable manufacturing, and particularly discloses a double-core photovoltaic waterproof cable and a preparation method thereof. The double-core photovoltaic waterproof cable comprises a conductor core, an insulation layer, a waterproof layer, a metal sheath and an outer sheath in sequence. The waterproof layer comprises the following raw materials in parts by weight: hydrogenated petroleum resin 30-40 parts, modified sepiolite fiber 5-10 parts and polyamide wax 10-20 parts. The modified sepiolite fiber is obtained by acidification modification treatment of sepiolite fiber. The double-core photovoltaic waterproof cable obtained by the application has the highest tensile strength, elongation at break and volume resistance retention rate of 91%, 93% and 99% respectively after water resistance test, and the waterproof performance of the double-core photovoltaic cable is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of cable manufacturing technology, and more specifically, to a dual-core photovoltaic waterproof cable and its preparation method. Background Technology

[0002] In recent years, my country's new energy power generation industry has developed rapidly, especially the photovoltaic power generation industry. Solar energy technology will become one of the future green energy technologies. Photovoltaic cables are a type of wire specifically designed for solar photovoltaic power generation systems, mainly used to transmit the electricity generated by solar panels to homes or businesses. Compared with single-core photovoltaic cables, dual-core photovoltaic cables improve conductivity and power transmission performance, reduce power loss during transmission, and increase tensile strength. Dual-core photovoltaic cables must be laid outdoors in harsh environmental conditions. Although they have high tensile strength, their water resistance is poor, making them unsuitable for use in humid and salt spray environments.

[0003] In related technologies, a polyethylene waterproof layer is wrapped around the surface of the conductor core to improve the waterproof performance of photovoltaic cables, but the waterproof performance is still relatively poor. Summary of the Invention

[0004] To improve the waterproof performance of dual-core photovoltaic cables, this application provides a dual-core waterproof photovoltaic cable and its preparation method.

[0005] In the first aspect, this application provides a dual-core photovoltaic waterproof cable, which adopts the following technical solution: A dual-core photovoltaic waterproof cable comprises, in sequence, a conductor core, an insulation layer, a waterproof layer, a metal sheath, and an outer sheath; the waterproof layer comprises the following raw materials in parts by weight: 30-40 parts hydrogenated petroleum resin, 5-10 parts modified sepiolite fiber, and 10-20 parts polyamide wax; the modified sepiolite fiber is obtained by acid modification treatment of sepiolite fiber.

[0006] By adopting the above technical solutions, the waterproof layer can improve the water-blocking ability of the dual-core photovoltaic cable, thereby preventing moisture from entering the insulation layer and ensuring the normal conductivity of the conductor core. Hydrogenated petroleum resin, as the main raw material of the waterproof layer, has high viscosity and adhesion, which can improve the waterproof effect. The modified sepiolite fiber undergoes acid treatment, which on the one hand removes carbonate impurities inside the sepiolite fiber and clears impurities from the pores; on the other hand, it modifies the pore size and structure, increasing microporosity and thus improving the sepiolite's ability to adsorb water, thereby further improving the waterproof effect of the dual-core photovoltaic cable. The added polyamide wax has excellent thixotropic properties, anti-sagging ability, and anti-settling ability, as well as very good strength and heat resistance, and good storage stability.

[0007] Preferably, the modified sepiolite fiber is prepared through the following steps: Sepiolite fibers were placed in a 1.5-2 mol / L hydrochloric acid solution, and 30-40% of the mass of the sepiolite fibers in a composite dispersant were added. The mixture was stirred at a constant temperature of 55-65℃ for 1.5-2.5 h, centrifuged, and the precipitate was collected. The precipitate was washed with deionized water until neutral, dried, calcined at 300-500℃ for 2-3 h, and pulverized to obtain modified sepiolite fibers. The mass ratio of the pretreated sepiolite fiber to the hydrochloric acid solution is 1:(8-12); the composite dispersant is a mixture of sodium hexametaphosphate and triethylhexylphosphoric acid.

[0008] By employing the above technical solution, the concentration of hydrochloric acid can be adjusted. Excessive hydrochloric acid concentration can damage the pores of sepiolite fibers, leading to a smaller specific surface area and thus affecting the adsorption capacity of the sepiolite fibers. Increasing the acidification temperature can accelerate the dissolution of some metal compounds in the sepiolite fibers, increasing the pore size and specific surface area. However, the temperature should not be too high, as this would cause the hydrochloric acid to volatilize and alter the concentration of the hydrochloric acid solution.

[0009] A compound dispersant is added, in which sodium hexametaphosphate can maintain the relative stability of sepiolite fibers in hydrochloric acid solution and improve the modification effect of sepiolite fibers, while triethylhexyl phosphate can further improve the dispersion effect of sodium hexametaphosphate on sepiolite fibers.

[0010] In addition, the sepiolite fiber is calcined to remove adsorbed water, zeolite water, crystal water and structural water between the sepiolite fibers and in the pores. The silanol groups on the surface are transformed into silicon-oxygen tetrahedral structures, which expands the channel size in the sepiolite, increases its specific surface area and enhances its adsorption performance, thereby improving the water absorption of the sepiolite fiber and preventing water from entering the cable and damaging the conductor core.

[0011] Preferably, the mass ratio of sodium hexametaphosphate to triethylhexylphosphoric acid is 1:(2-3).

[0012] By adopting the above technical solution and adjusting the mass ratio of sodium hexametaphosphate to triethylhexylphosphoric acid, the modification effect of sepiolite fiber can be further improved, thereby enhancing the waterproof performance of dual-core photovoltaic cables.

[0013] Preferably, the outer sheath comprises the following raw materials in parts by weight: 80-120 parts of polyvinyl chloride resin, 40-60 parts of plasticizer, 10-20 parts of nano silica, 4-5 parts of polyvinyl acetate, and 1-3 parts of antioxidant 1010.

[0014] By adopting the above technical solution, the nano-silica in the outer sheath material has a large specific surface area and excellent adsorption performance. On the one hand, it enhances the strength of the sheath, and on the other hand, it has a certain adsorption capacity for moisture, preventing moisture from penetrating into the cable interior and improving the waterproof performance of the dual-core photovoltaic cable. The addition of polyvinyl acetate can further improve the dispersibility of nano-silica, thereby further improving the waterproof performance of the outer sheath.

[0015] Preferably, the weight ratio of the polyvinyl acetate to nano-silica is 1:(3-4).

[0016] By adopting the above technical solution and adjusting the weight ratio of polyvinyl acetate to nano silica, the dispersibility of nano silica in the outer sheath raw material system can be further improved.

[0017] Preferably, the outer sheath further includes the following raw materials in parts by weight: 4-14 parts of an aqueous solution of potassium methylsilicate with a solid content of 35-45%.

[0018] By adopting the above technical solution, potassium methylsilicate has good hydrophobic properties, as well as density and waterproofing effect, and its addition improves the waterproofness of nano silica.

[0019] Preferably, the weight ratio of the potassium methylsilicate aqueous solution to nano-silica is 1:(2-3).

[0020] By adopting the above technical solution and adjusting the weight ratio of potassium methylsilicate aqueous solution to nano-silica, the water resistance of nano-silica can be further improved.

[0021] Secondly, this application provides a method for preparing a dual-core photovoltaic waterproof cable, which adopts the following technical solution: A method for preparing a dual-core photovoltaic waterproof cable includes the following steps: S1. Mix, knead, and granulate the outer sheath raw materials to obtain the outer sheath; S2. Mix the waterproof layer raw materials, stir evenly, knead, and granulate by extrusion to obtain the waterproof layer; S3. Copper monofilaments are drawn, annealed, and stranded to obtain conductor cores. An insulation layer is extruded and filled with polypropylene. The waterproof layer, metal sheath, and outer sheath are extruded onto the surface of the insulation layer in sequence. After cooling and curing, the cable is cut to obtain a dual-core photovoltaic waterproof cable.

[0022] In summary, this application has the following beneficial effects: (1) By controlling the types and dosages of raw materials in the dual-core photovoltaic cable, this application improves the waterproof performance of the dual-core photovoltaic waterproof cable by making its tensile strength, elongation at break and volume resistivity retention rate 87%, 88% and 95% respectively after water resistance test.

[0023] (2) This application improves the waterproofness of the dual-core photovoltaic waterproof cable by adjusting the mass ratio of sodium hexametaphosphate to triethylhexylphosphoric acid during the preparation of modified sepiolite fiber, so that the tensile strength, elongation at break and volume resistivity retention rate of the dual-core photovoltaic waterproof cable after water resistance test are 88-89%, 89-90% and 96-97%, respectively.

[0024] (3) This application improves the waterproofness of the dual-core photovoltaic cable by adding potassium methylsilicate aqueous solution to the outer sheath material and adjusting the weight ratio of potassium methylsilicate aqueous solution to nano silica. The tensile strength, elongation at break and volume resistivity retention rate of the dual-core photovoltaic waterproof cable after water resistance test are 90-91%, 91-93% and 98-99% respectively. Detailed Implementation

[0025] The present application will be further described in detail below with reference to the embodiments.

[0026] The following raw materials used in this application are all commercially available products and are intended to fully disclose the raw materials used in this application. They should not be construed as limiting the source of the raw materials. Specifically: the plasticizer is diisodecyl adipate with an effective substance content of 99%; hydrogenated petroleum resin with a solid content of 99%; polyamide wax with an effective substance content of 99.9%; sepiolite fiber with a specification of 4-8 mm and a particle size of 300 mesh; sodium hexametaphosphate with an effective substance content of 99%; triethylhexyl phosphate with an effective substance content of 99%; polyvinyl chloride resin with a solid content of 90%; nano silica with a particle size of 325 mesh; polyvinyl acetate with an effective substance content of 99.9%; the conductor core is a copper core; the insulation layer is a cross-linked polyethylene insulation layer; and the metal sheath is a stainless steel flexible metal tube.

[0027] The following are examples of the preparation of modified sepiolite fibers. Preparation Example 1 A modified sepiolite fiber is prepared by the following steps: 1 kg of sepiolite fiber was placed in 10 L of 2 mol / L hydrochloric acid solution, and 350 g of composite dispersant was added. The mixture was stirred at 60 °C for 2 h, centrifuged, and the precipitate was collected. The precipitate was washed with deionized water until neutral, dried, calcined at 400 °C for 2 h, and then pulverized to obtain modified sepiolite fiber. The composite dispersant was a mixture of 175 g of sodium hexametaphosphate and 175 g of triethylhexyl phosphoric acid.

[0028] Preparation Examples 2-5 The modified sepiolite fibers prepared in Examples 2-5 were prepared using the same method as those prepared in Example 1, except that the masses of sodium hexametaphosphate and triethylhexylphosphoric acid in the composite dispersant were 117g and 233g, 100g and 250g, 87.5g and 262.5g, and 77.7g and 272.3g, respectively. The remaining operations were the same as those in Example 1.

[0029] Example 1 The dual-core photovoltaic waterproof cable of Example 1 is prepared through the following steps: S1. According to the dosage in Table 1, the outer sheath raw materials are mixed, kneaded, and extruded into granules to obtain the outer sheath; S2. According to the dosage in Table 2, the waterproof layer raw materials are mixed, stirred evenly, and then granulated by intensive mixing and extrusion to obtain the waterproof layer; wherein, the modified sepiolite fiber is selected from the modified sepiolite fiber prepared in Preparation Example 1. S3. Copper monofilaments are drawn, annealed, and stranded to obtain conductor cores. An insulation layer is extruded and filled with polypropylene. The waterproof layer, metal sheath, and outer sheath are extruded onto the surface of the conductor cores in sequence. After cooling and curing, the cores are cut to obtain a dual-core photovoltaic waterproof cable.

[0030] Examples 2-5 The preparation methods of the dual-core photovoltaic waterproof cables in Examples 2-5 are exactly the same as those in Example 1, except that the dosage of each raw material is different, as detailed in Tables 1 and 2.

[0031] Table 1. Raw material dosage for the outer sheaths of Examples 1-5 (unit: kg) Polyvinyl chloride resin 100 100 100 100 100 plasticizer 50 50 50 50 50 Nano silica 10 15 14 20 20 Polyvinyl acetate 5 5 4 5 4 antioxidants 4 4 4 4 4 Table 2. Proportions of each raw material in the waterproofing layer of Examples 1-5 (unit: kg) Hydrogenated petroleum resin 35 35 35 35 35 Modified sepiolite fiber 5 5 5 5 5 Polyamide wax 15 15 15 15 15 Examples 6-7 The preparation method of the dual-core photovoltaic waterproof cable in Examples 6-7 is exactly the same as that in Example 1, except that the dosage of each raw material is different, as detailed in Table 3.

[0032] Table 3. Proportion of each raw material in the waterproofing layer of Examples 6-7 (unit: kg) Hydrogenated petroleum resin 35 35 Modified sepiolite fiber 8 10 Polyamide wax 15 15 Examples 8-11 The preparation method of the dual-core photovoltaic waterproof cable in Examples 8-11 is exactly the same as that in Example 1. The difference is that the modified sepiolite fiber is the modified sepiolite fiber prepared in Examples 2-5, and the other raw materials and dosages are the same as in Example 1.

[0033] Examples 12-16 The preparation method of the dual-core photovoltaic waterproof cable in Examples 12-16 is exactly the same as that in Example 1. The difference is that the outer sheath material also includes an aqueous solution of potassium methylsilicate with a solid content of 35-45%, as detailed in Table 4.

[0034] Table 4. Raw material dosage for the outer sheaths of Examples 12-16 (unit: kg) Polyvinyl chloride resin 100 100 100 100 100 plasticizer 50 50 50 50 50 Nano silica 14 14 14 14 14 Polyvinyl acetate 4 4 4 4 4 antioxidants 4 4 4 4 4 Potassium methylsilicate aqueous solution 14 7 5.6 4.6 4 Comparative Example 1 The preparation method of the dual-core photovoltaic waterproof cable of Comparative Example 1 is exactly the same as that of Example 1, except that modified sepiolite fiber is not added to the waterproof layer raw material, while the other raw materials and dosages are the same as those of Example 1.

[0035] Comparative Example 2 The preparation method of the dual-core photovoltaic waterproof cable of Comparative Example 2 is exactly the same as that of Example 1, except that the modified sepiolite fiber in the waterproof layer raw material is replaced with sepiolite fiber in equal amounts, and the remaining raw materials and dosages are the same as those in Example 1.

[0036] Comparative Example 3 The preparation method of the dual-core photovoltaic waterproof cable of Comparative Example 3 is exactly the same as that of Example 1, except that no waterproof layer is set. Otherwise, it is the same as Example 1.

[0037] Performance Testing (Part 1) The waterproof performance of the dual-core photovoltaic waterproof cables obtained in different Examples 1-16 and Comparative Examples 1-3 was tested using the following testing standards or methods. The test results are detailed in Table 5.

[0038] Salt water resistance test: The dual-core photovoltaic waterproof cable was immersed in a 5wt% sodium chloride solution for 336 hours at a depth of 300 mm and a temperature of 90±2℃. The retention rate of tensile strength and elongation at break after the salt water resistance test was then measured.

[0039] Table 5 Performance test results of different dual-core photovoltaic waterproof cables The test results in Table 5 show that the dual-core photovoltaic waterproof cable obtained in this application has the highest tensile strength, elongation at break, and volume resistivity retention rate after water resistance test, which are 91%, 93%, and 99%, respectively, thus improving the waterproof performance of the dual-core photovoltaic cable.

[0040] In Examples 1-5, the tensile strength, elongation at break, and volume resistivity retention of the dual-core photovoltaic waterproof cables of Examples 2-4 after water resistance tests were 85-86%, 86-87%, and 93-94%, respectively, all higher than those of Examples 1 and 5. This indicates that a weight ratio of polyvinyl acetate to nano-silica in the outer sheath material of 1:(3-4) is more suitable, improving the waterproof performance of the dual-core photovoltaic cable. This may be related to the fact that the addition of polyvinyl acetate can further improve the dispersibility of nano-silica, thereby further improving the waterproof performance of the outer sheath.

[0041] Based on the performance test results of the cables in Examples 3 and 6-7, the tensile strength, elongation at break, and volume resistivity retention rate of the dual-core photovoltaic waterproof cable in Example 6 after the water resistance test were 87%, 88%, and 95%, respectively, all higher than those in Examples 3 and 7. This indicates that the amount of modified sepiolite fiber in the waterproof layer of Example 6 is more appropriate, improving the waterproof performance of the dual-core photovoltaic cable. This may be related to the acidification treatment of the modified sepiolite fiber, which on the one hand removes carbonate impurities inside the sepiolite fiber and clears impurities from the pores, and on the other hand modifies the pore size and structure, increasing the microporosity and thus improving the sepiolite's ability to adsorb water, thereby further improving the waterproof effect of the dual-core photovoltaic cable.

[0042] Based on the performance test results of cables from Examples 6 and 8-11, the tensile strength, elongation at break, and volume resistivity retention rates of the dual-core photovoltaic waterproof cables from Examples 8-10 after water resistance tests were 88-89%, 89-90%, and 96-97%, respectively, all higher than those of Examples 6 and 11. This indicates that a mass ratio of sodium hexametaphosphate to triethylhexylphosphoric acid of 1:(2-3) is more suitable when preparing modified sepiolite fibers, thus improving the waterproof performance of the dual-core photovoltaic cables. This may be related to the fact that adjusting the mass ratio of sodium hexametaphosphate to triethylhexylphosphoric acid can further enhance the modification effect of sepiolite fibers, thereby improving the waterproof performance of the dual-core photovoltaic cables.

[0043] In Examples 12-16, the tensile strength, elongation at break, and volume resistivity retention of the dual-core photovoltaic waterproof cables of Examples 13-15 after water resistance tests were 90-91%, 91-93%, and 98-99%, respectively, all higher than those of Examples 12 and 16. This indicates that a weight ratio of potassium methylsilicate aqueous solution to nano-silica in the outer sheath material of 1:(2-3) is more suitable, improving the waterproof performance of the dual-core photovoltaic cable. This may be related to the fact that potassium methylsilicate has good hydrophobic properties and provides both density and waterproofing, and its addition enhances the waterproof performance of nano-silica.

[0044] Based on the performance test data of cables in Example 1 and Comparative Examples 1-3, it was found that adding modified sepiolite fiber to the waterproof layer material of dual-core photovoltaic cables can improve the waterproof performance of dual-core photovoltaic cables.

[0045] Performance Testing (Part 2) The basic performance of the dual-core photovoltaic waterproof cables obtained in different Examples 1, 6, 9, 14 and Comparative Examples 1-3 was tested using the following testing standards or methods. The test results are detailed in Table 6.

[0046] Tensile strength and elongation at break: The tensile strength and elongation at break of the dual-core photovoltaic cable were tested in accordance with GB / T2951-2008 "Test Methods for Mechanical and Physical Properties of Cables".

[0047] Single-strand vertical combustion: Tested according to GB / T18380-2008 "Cable and optical fiber cable combustion test under flame conditions".

[0048] Table 6 Performance test results of different dual-core photovoltaic waterproof cables The test results in Table 6 show that the dual-core photovoltaic waterproof cable obtained in this application has the highest tensile strength and elongation at break of 30.5 MPa and 370%, respectively, and can pass the vertical burning test for a single cable, demonstrating high comprehensive performance.

[0049] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A dual-core photovoltaic waterproof cable, characterized in that, The material comprises, in sequence, a conductor core, an insulation layer, a waterproof layer, a metal sheath, and an outer sheath; the waterproof layer comprises the following raw materials in parts by weight: 30-40 parts hydrogenated petroleum resin, 5-10 parts modified sepiolite fiber, and 10-20 parts polyamide wax; the modified sepiolite fiber is obtained by acid-modifying sepiolite fiber. The modified sepiolite fiber is prepared through the following steps: Sepiolite fibers were placed in a 1.5-2 mol / L hydrochloric acid solution, and 30-40% of the mass of the sepiolite fibers in a composite dispersant was added. The mixture was stirred at a constant temperature of 55-65℃ for 1.5-2.5 h, centrifuged, and the precipitate was collected. The precipitate was washed with deionized water until neutral, dried, calcined at 300-500℃ for 2-3 h, and pulverized to obtain modified sepiolite fibers. The mass ratio of sepiolite fiber to hydrochloric acid solution is 1:(8-12); the composite dispersant is a mixture of sodium hexametaphosphate and triethylhexylphosphoric acid; The outer sheath comprises the following raw materials in parts by weight: 80-120 parts of polyvinyl chloride resin, 40-60 parts of plasticizer, 10-20 parts of nano silica, 4-5 parts of polyvinyl acetate, and 1-3 parts of antioxidant 1010.

2. The dual-core photovoltaic waterproof cable according to claim 1, characterized in that, The mass ratio of sodium hexametaphosphate to triethylhexylphosphoric acid is 1:(2-3).

3. The dual-core photovoltaic waterproof cable according to claim 1, characterized in that, The weight ratio of polyvinyl acetate to nano-silica is 1:(3-4).

4. The dual-core photovoltaic waterproof cable according to claim 1, characterized in that, The outer sheath also includes the following raw materials in parts by weight: 4-14 parts of potassium methylsilicate aqueous solution with a solid content of 35-45%.

5. The dual-core photovoltaic waterproof cable according to claim 4, characterized in that, The weight ratio of the potassium methylsilicate aqueous solution to nano-silica is 1:(2-3).

6. A method for preparing a dual-core photovoltaic waterproof cable according to any one of claims 1-5, characterized in that, Includes the following steps: S1. Mix, knead, and granulate the outer sheath raw materials to obtain the outer sheath; S2. Mix the waterproof layer raw materials, stir evenly, knead, and granulate by extrusion to obtain the waterproof layer; S3. Copper monofilaments are drawn, annealed, and stranded to obtain conductor cores. An insulation layer is extruded and filled with polypropylene. The waterproof layer, metal sheath, and outer sheath are extruded onto the surface of the insulation layer in sequence. After cooling and curing, the cable is cut to obtain a dual-core photovoltaic waterproof cable.

Citation Information

Patent Citations

  • High-performance insulating waterproof photovoltaic cable

    CN110240765A

  • Network combined cable and preparation process thereof

    CN114456516A